Perovskite Solar Cells for Space Applications: Progress and Challenges - Tu, Yongguang; Wu, Jiang; Xu, Guoning; Yang, Xiaoyu; Cai, Rong; Gong, Qihuang; Zhu, Rui; Huang, Wei (Advanced materials (Weinheim), 2021)
Metal halide perovskites have aroused burgeoning interest in the field of photovoltaics owing to their versatile optoelectronic properties. The outstanding power conversion efficiency, high specific power (i.e., power to weight ratio), compatibility with flexible substrates, and excellent radiation resistance of perovskite solar cells (PSCs) enable them to be a promising candidate for next‐generation space photovoltaic technology. Nevertheless, compared with other practical space photovoltaics, such as silicon and III‐V multi‐junction compound solar cells, the research on PSCs for space applications is just in the infancy stage. Therefore, there are considerable interests in further strengthening relevant research from the perspective of both mechanism and technology. Consequently, the approaches used for and the consequences of PSCs for space applications are reviewed. This review provides an overview of recent progress in PSCs for space applications in terms of performance evolution and mechanism exploration of perovskite films and devices under space extreme environments. Perovskite solar cells (PSCs) are considered as promising candidates for next‐generation space photovoltaic technology. Key space environments and specific requirements for space photovoltaics are outlined. Some recent advances in terms of performance evolution and mechanism exploration of perovskite films and devices under space extreme environments are summarized. Progress and challenges associated with space applications of PSCs are highlighted.